Built Infrastructure Renewal and Climate Change Mitigation Can Both Find Solutions in CO2 - Henrion, Lucca; Zhang, Duo; Li, Victor; Sick, Volker (Frontiers in Sustainability, 2021)
From technology to policy, the US is thinking about construction differently. The federal government is motivated to address the aging infrastructure across the country, and policy proposals are surfacing that seek green methods of performing this construction. This paper reviews the current status of concrete technology and policy to provide insight into the current state of the art. The scale of CO2 emissions from concrete production and use is elucidated. Current embodied emissions reduction methods show that action can be taken today in small and large projects alike. Additionally, developing concrete technologies offers pathways to reuse and rely on concrete for longer service lifetimes and reduce their lifetime embodied emissions. These concrete technologies must be implemented, and public procurement proves a unique tool to develop a nationwide demand signal for low embodied carbon building materials. Local governments closely interact with concrete producers, state governments oversee large infrastructure projects, and the federal government invests massively in construction. All three levels of government must coordinate for the effective rollout of low embodied carbon construction practices. Disparate policy approaches show successes and pitfalls to developing an effective construction policy that is aligned with climate. Importantly, approaches to addressing the twin challenge of climate change and crumbling infrastructure must consider the whole lifetime of the concrete. Throughout this paper, we examine the sector to highlight current practices and provide a vision for effective implementation.